Os anúncios no Jornal A União (1904-1937): a propagação da modernidade pedagógica na Paraíba - Arruda, Kalyne Barbosa (2015)
This study has the analysis of the education representations present in the reports about teachers, schools, and teach methods in The Union Journal, at 1904 to 1930, as general objective. So, the identified reports show a representation of schools, teachers and teach methods, having been a consolidation and divulgation asset of the school identifies, when the teachers were shown as a quality element, certifying the success of educational and professional institutions. Using Chartier’s studies as reference, planed to work how the support texts and printouts organize the reading that might be done of them. This study used the Ginsburg’s index paradigm (1989) also, because that was the useful flair, the jab view, the intuition, during the search with reports about education in journals. In this manner, motivated by the historiographical search dimension and the desire of contributing to the Paraíba education history, parting by The Union Journal reports, the present search intends to collaborate with the studies that discuss reports, educational representations and pedagogical modernity in XX century first years.